Clash of Cultures: Implications of China’s Belt and Road Initiative (BRI) into Myanmar - Bhasin, Balbir; Ng, Lee Keng; Zeng, Yanping (Center for Southeast Asian Social Studies (CESASS), 2023)
China has embarked on a massive infrastructure development project across and through its Southeast Asian neighbors such as the China-Myanmar Economic Corridor (CMEC). While China is the world's second largest economy, Myanmar is on the United Nations' list of 48 least developed countries (LDCs) with over 70% of the population living in rural areas and depend on agriculture. While China has no religion Myanmar's culture is immersed in Theravada Buddhism. We used a dataset from the World Values Survey to analyze the cultural variances based on the Value-Orientation Framework. Our findings show that the two countries differ significantly in almost all of the value orientations. Challengers such as a lack of a common history, religion and language had already raised tensions and conflicts in past projects and would lead to an erosion of the project-benefits upon the completion of the CMEC. This paper highlights the implications and pitfalls to avoid for both countries.